The Formation of the New Autonomous Region of Papua and Welfare Guarantees in the Decentralization Policy - Hendy Setiawan; Genut Wahyu Widiono; Galuh Hikmah (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
The instrument for regional structuring, particularly regional expansion leading to new autonomous regions, can be seen as a rational and logical implication of decentralization implementation. Decentralization, in turn, played a pivotal role in shaping the grand design of regional planning (Desertada) up until the imposition of a regional expansion moratorium in late 2009. This research employs a qualitative methodology, a case study approach, chosen due to its adaptability and effectiveness in addressing dynamic and unpredictable social contexts. The focal point of this study revolved around the narratives underlying the formation of new autonomous regions (DOB) in Papua, particularly emphasizing the discourse on welfare. The government has actively promoted narratives of welfare motives and national strategic interests. The government has actively promoted narratives of welfare motives and national strategic interests. Despite the expansion of the Papua region and the implementation of special autonomy, it is observed that these initiatives have not significantly contributed to development. Notably, the expansion process in Papua, marred by alleged procedural and material deficiencies, took place without indigenous Papuans' meaningful participation and consultation.